Developing a Framework for Infrastructure & Facility Asset Management Knowledge & Science Development by Using Concept Mapping - Suprayitno, Hitapriya; Asih Aryani Soemitro, Ria (Jurnal Manajemen Aset Infrastruktur & Fasilitas, 2018)
Infrastructure and Facility are capital for regionâ€™s life. Therefore, Infrastructure & Facility Asset Management Knowledge must be developed and implemented. Jurnal Manajemen Aset Infrastruktur & Fasilitas was established for developing this. The development needs a framework. A Knowledge Development Framework has been thought and formulated. The framework is presented by concept mapping. It consists ofÂ  an Infrastructure & Facility Asset Management Conceptual Model, an Infrastructure & Facility Asset Management Basic Model and 6 Basic Knowledges. The 6 Basic Knowledges are about : the Infrastructure & Facility, Infrastructure & Facility Managing Organization, Infrastrucutre & Facility Asset Management, Organization Management, Tools for Analyses, and Related Software can be used for Asset Management